The harnessing of power : how 19th century transport innovators transformed the way the world operates - Lay, M. G. (Maxwell G.) (Cambridge Scholars Publishing, 2018)
This book examines how the 19th century's transport legacy of bicycles, trains, ocean-going steamers, trucks, trams, buses and cars arose, creating numerous new technologies and markets. Nothing like this range of transport changes had occurred before, and the 20th century changes were incremental compared with those of the 19th century. The book explores where the key transport features came from, and why there were so many inventions, innovations, and inconsistencies. The Industrial Revolution was a key part of the process as it had strong links with transport developments. This text adopts.